Biodegradable Pancreatic and Biliary Stents—Still Searching For Disappearing Wonder? - Daniel, Philip; Rana, Surinder S. (Journal of Digestive Endoscopy, 2020)
Biodegradable stents hold considerable promise in the treatment of benign biliary or pancreatic diseases with the major advantage being avoidance of repeated interventions for stent removal or stent exchange. They have been confirmed to have good biocompatibility and current evidence shows acceptable rates of clinical efficacy and safety. In the current news and views, we discuss an interesting study that has evaluated a new type of biodegradable biliary and pancreatic stent (the Archimedes stent) in benign biliary and pancreatic diseases.
Keywords: pancreatitis; stent; stricture